Legal Protection of Policyholders Due to Bankruptcy of Bumi Asih Jaya Insurance - Danggur Feliks (UIN Sunan Gunung Djati, 2022)
PT. Asuransi Bumi Asih JayaInsurance or Asuransi Bumi Asih JayaÂ failed to pay due to many factors, one of which was due to the Covid-19 pandemic. This condition caused the investment portfolio of the two products to be problematic. After experiencing a default, the Supreme Court finally decided to go bankrupt. So that policyholders must get legal protection from the bankruptcy of Krishna Life. The formulation of the problem in this research is the legal position of the policyholder against the decision of the bankrupt Asuransi Bumi Asih Jayaand the legal protection of the Asuransi Bumi Asih Jayapolicy holder being declared bankrupt. This study also uses a normative juridical research method. As well as using a statutory approach and a conceptual approach. Based on the results of research and discussion of the legal position between Asuransi Bumi Asih Jayaand policyholders under Preferred Creditors and above Concurrent Creditors. Then there is also no legal relationship between Krishna Life and the Policy Holder. This provision is regulated in Article 21 of the Bankruptcy Law/PKPU, so during the bankruptcy process, the assets obtained from Krishna Life are still managed by the Curator because there has been a bankruptcy statement from the Supreme Court Judge at the cassation level. So that there is no legal relationship again between the Insurer, namely Krishna Life and the Insured, namely the policyholder. Legal protection for Asuransi Bumi Asih JayaInsurance even though it has been declared bankrupt based on Article 52 paragraph 1 of the Insurance Law. Asuransi Bumi Asih Jaya Insurance also has the same position and is entitled to obtain the proceeds from the sale of the debtor's assets, both the debtor's assets in the future. The bankruptcy estate settlement process from Life Insurance can be carried out by a Curator who starts the settlement of the bankruptcy estate after the bankruptcy estate is unable to pay and the debtor's business is terminated.